Observation of Near Earth Asteroids (NEA) at the Abastumn Astrophysical Observatory - Ayvazyan, V.; Inasaridze, R.; Krugli, Yu.; Zhuzhuiadze, D.
In this paper, the objects of study are near-Earth asteroids, or NEA for short. They are small solid celestial bodies that closely approach or intersect the Earth’s orbit. From a scientific point of view, NEA approaches to the Earth allow us to study cosmic bodies. On the other hand, the importance of studying NEA is justified by the danger of these bodies falling to the Earth and causing catastrophic events. The fall of NEAs to the Earth’s surface is a proven fact. Such events occurred in the past history of the Earth, are occurring at present and are expected in the future. Therefore, in order to predict such falls and understand the degree of danger, it is necessary to discover new NEAs and study them. Regular photometric observations of NEAs are carried out at the Abastumani Observatory, which are primarily the observatory’s contribution to solving the global problem of ”Asteroid Hazard”. The study of asteroids in Abastumani will be continued by conducting their optical observations in selected areas of research.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture